2014
DOI: 10.2478/10004-1254-65-2014-2547
|View full text |Cite
|
Sign up to set email alerts
|

In vivo changes in carbonic anhydrase activity and histopathology of gill and liver tissues after acute exposure to chlorpyrifos in rainbow trout

Abstract: Chlorpyrifos is an organophosphate pesticide widely used in agriculture and aquaculture. This study investigated its effects on carbonic anhydrase (CA) enzyme activity and histopathology of rainbow trout gill and liver. The fish were exposed to 2.25 (25 % of 96 h LC 50 ), 4.5 (50 % of 96 h LC 50 ), and 6.75 µg L -1 (75 % of 96 h LC 50 ) of chlorpyrifos for 24, 48, 72, and 96 h. CA activity was measured in liver and gills and histopathological changes were examined by light microscopy. The most common liver cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 42 publications
(31 reference statements)
3
40
1
Order By: Relevance
“…This decline may be related to changes in the inner mitochondrial membrane permeability caused by lipid peroxidation. A time-dependent decrease in carbonic anhydrase activity was reported in fish exposed to chlorpyrifos (35). Carbonic anhydrase in hepatocyte mitochondria plays a vital role in the regulation of ionic balance, which is required in metabolic reactions, production of ATP, and transport processes (102).…”
Section: Biochemical Evidence Of Op Hepatotoxicitymentioning
confidence: 99%
See 2 more Smart Citations
“…This decline may be related to changes in the inner mitochondrial membrane permeability caused by lipid peroxidation. A time-dependent decrease in carbonic anhydrase activity was reported in fish exposed to chlorpyrifos (35). Carbonic anhydrase in hepatocyte mitochondria plays a vital role in the regulation of ionic balance, which is required in metabolic reactions, production of ATP, and transport processes (102).…”
Section: Biochemical Evidence Of Op Hepatotoxicitymentioning
confidence: 99%
“…OPs are oxidants and impair enzymatic antioxidant defences, including superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPx), and glutathione S-transferase (GST) (23,34,44,(114)(115)(116)(117)(118)(119)(120)(121)(122)(123)(124)(125)(126)(127)(128)(129). Malathion, methyl parathion, and parathion in HepG2 cell lines, as well as chlorpyrifos, methidathion, chlorfenvinphos, and dimethoate in rat liver and diazinon in fish most probably disrupt membrane lipids through oxidative stress (23,35,61,116,118,(130)(131)(132)(133)(134)(135). Table 1 summarises the key changes in antioxidant defence and oxidative stress biomarkers caused by OPs.…”
Section: Possible Effects Of Ops On Hepatic Oxidative Stress Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…Carbonic anhydrase is a zinc metalloenzyme having an important role in the removal and exchange of CO 2 between the blood and tissues in fish, and is also responsible for catalyzing the reversible hydration/dehydration of CO 2 to form bicarbonate and protons (Esbaugh and Tufts, 2006). Several previous studies have reported decreases in gill CA activity as a result of exposure to toxicants (Ceyhun et al, 2010;Topal et al, 2014;Ali et al, 2015). However, no studies investigating the impacts of cyanobacterial neurotoxins or PSPs on CA activity in the gills of fish have been published.…”
Section: Inhibition Of Ca Activity In the Gills Of Aphantoxin-exposedmentioning
confidence: 99%
“…Therefore, alterations in branchial physiological function may serve as crucial biomarkers of exposure to environmental challenges (Brunelli et al, 2011). Alterations in gill ultrastructure, reactive oxygen species (ROS), total antioxidative capacity (T-AOC), and the activities of carbonic anhydrase (CA), Na + -K + -ATPase (NKA), and lactate dehydrogenase (LDH) are sensitive and valuable parameters that can be used to assess the impacts of exposure to many anthropogenic or natural pollutants (Pandey et al, 2008;Shimomura et al, 2012;Topal et al, 2014). Previous studies have associated abnormalities in these parameters with exposure to pesticides, metals, and other toxicants (Suvetha et al, 2010;Atli and Canli, 2013;Kaur and Kaur, 2015).…”
Section: Introductionmentioning
confidence: 99%